UPAYA REBRANDING PANTAI JEBRING SEBAGAI DESTINASI WISATA HALAL UNGGULAN MELALUI DIGITALISASI WISATA DI KABUPATEN BLITAR - Moch Khoirul Anwar; Moh Farih Fahmi; Rachmad Syaifudin; Ahmad Nurdjayanto (JANITA : JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Efforts to rebrand Jebring Beach in Ngadipuro Village, Wonotirto District, Blitar Regency, as a leading halal tourist destination through digitalization are an important step in increasing tourist attraction and visits. The importance of this topic is driven by tourism potential which has not been maximized and the need for facilities that are halal tourism friendly. The method used in this service is Community Based Research (CBR), involving active community participation in planning and implementation. The results of this effort show a significant increase in the number of visits and visitor satisfaction after digitalization, as well as the formation of a positive image of Jebring Beach as a destination that meets the needs of Muslim tourists. Thus, the results of this rebranding not only have an impact on marketing, but also contribute to local economic empowerment and cultural preservation. This shows that the integration of technology and a community-based approach can create sustainable and inclusive tourism destinations.